#Recurrence T(n)=3T(n/3)+Ѳ(log₃n) [closed] - recurrence

Closed. This question needs details or clarity. It is not currently accepting answers.
Want to improve this question? Add details and clarify the problem by editing this post.
Closed 5 years ago.
Improve this question
Sorry I have tried a lot to solve this recurrence equation
T (n) = 3T (n / 3) + Ѳ (log3n)
with the replacement method but I can not get the required result:
1) T (n) = O (nlogn)
2) Induction
Base: for every n = 1 -> 1log1 + 1 = 1 = T (1)
Inductive step: T (k) = klogk + k for each k <n
Use k = n / 3
T (n) = 3T (n / 3) + Ѳ (log₃n)
1) T (n) = O (nlogn)
2) Induction
Base: for every n = 1 -> 1log1 + 1 = 1 = T (1)
Inductive step: T (k) = klogk + k for each k <n
Use k = n / 3
T (n) = 3T (n / 3) + Ѳ (log₃n)
= 3 [n / 3logn / 3 + n / 3] + (log₃n)
= nlogn / 3 + n + (log₃n)
= n(logn-log3) + n + (log₃n)
= nlogn-nlog3 + n + (log3n)

Firstly we can (eventually) ignore the base 3 in the Theta-notation, as it amounts to a multiplicative factor as is therefore irrelevant. Then we can try the following method:
1. Hypothesis by inspection:
If we re-substitute T into itself multiple times, we get:
What is the upper limit m? We need to assume that T(n) has a stopping condition, i.e. some value of n where it stops recursing. Assuming that it is n = 1 (it really doesn't matter, as long as it's a constant much smaller than n). Continuing (and briefly restoring the base 3):
Surprisingly the answer is not Ө(n log n).
2. Induction base case
We don't use induction to prove the final result, but the series result we deduced by inspecting the behaviour of the expansion.
For the base case n / 3 = 1, we have:
Which is consistent.
3. Induction recurrence
Again, consistent. Thus by induction the summation result is correct, and T(n) is indeed Ө(n).
4. Numerical tests:
Just in case you still cannot believe that it is Ө(n), here is a numerical test to prove the result.
Javascript code:
function T(n) {
return n <= 1 ? 0 : 3*T(floor(n/3)) + log(n);
}
Results:
n T(n)
--------------------------
10 5.598421959
100 66.33828212
1000 702.3597066
10000 6450.185742
100000 63745.45154
1000000 580674.1886
10000000 8924162.276
100000000 81068207.64
Graph:
The linear relationship is clear.

Related

Write Recurrence for Given Function

I am trying to write the recurrence relation for the running time of the following function:
function G(n):
if n>0 then:
x=0
for i = 1 to n:
x = x + 1
G(n-1)
end if
What I came up with was:
T(n) = 1 if n <= 0
T(n) = T(n-1) + 1 if n>0
However I was told that this was incorrect and I don't know why or what the correct solution would be. Any help is greatly appreciated!
T(n) = 1 if n <= 0
T(n) = T(n-1) + O(n) if n>0
Instead of O(1), it should be O(n), because you are looping from 1 to n
If you solve the recurrence, the overall complexity will be O(n2)

Is an admisible heuristic always monotone (consistent)?

For the A* search algorithm, provided an heuristic h, supose h is admisible.
That is:
h(n) ≤ h*(n) for every node n, where h* is the real cost from n to goal.
Does this ensure the heuristic is monotone?
That is:
f(n) ≤ g(n') + h(n') for every sucesor n' of n, where f(n)= h(n) + g(n) and g(n) is the accumulated cost.
No.
Assume you have three successor states s1, s2, s3 and a goal state g so that s1 -> s2 -> s3 -> g.
s1 is the starting node.
Consider also the following values for h(s) and h*(s) (i.e. true cost):
h(s1) = 3 , h*(s1) = 6
h(s2) = 4 , h*(s2) = 5
h(s3) = 3 , h*(s3) = 3
h(g) = 0 , h*(g) = 0
Following the only path to the goal we can have that:
g(s1) = 0, g(s2) = 1, g(s3) = 3, g(g) = 6, coinciding with the true cost above.
Although the heuristic function is admissible (h(s) <= h*(s)), f(n) will not be monotonic. For instance f(s1) = h(s1) + g(s1) = 3 while f(s2) = h(s2) + g(s2) = 5 with f(s1) < f(s2). Same holds between f(s2) and f(s3).
Of course this means you have a quite uninformative heuristic.

Recurrence relation - equal roots of characteristic equation

I have the following problem:
Solve the following recurrence relation, simplifying your final answer
using 'O' notation.
f(0)=3
f(1)=12
f(n)=6f(n-1)-9f(n-2)
We know this is a homogeneous 2nd order relation so we write the characteristic equation: a^2-6a+9=0 and the solutions are a1,2=3.
The problem is when I replace these values I get:
f(n)=c1*3^n+c2*3^n
and using the 2 initial relations I have:
f(0)=c1+c2=3
f(1)=3(c1+c2)=12
which gives me that there no values such that c1 and c2 such that these 2 relation are true.
Am I doing something wrong? Is the way it should be solved different when it comes to identical roots for the characteristic equation?
You can't solve it this way, because your matrix A is not diagonalizable.
However, here is what you get if you use Jordan's normal form instead:
f(n) = 3^{n-1}(3n + 9)
The Jordan matrix and the basis (with notation from wikipedia + Octave) is:
J := [3,1;0,3]
P := [3,4;1,1]
such that PJP^{-1} = A, where
A := [6,-9;1,0]
is your recurrence matrix. Furthermore, the Jordan matrix is almost as good as a diagonal matrix for computing powers:
J^n = 3^(n-1) * [3,n;0,3].
The recurrence is then:
[f(n+1); f(n)] = A^n [12,3] = PJ^nP^-1[12,3] = (<whatever>, 3^(n-1)*(3n+9)).
Here a quick numerical check (Scala, but you can take whatever you want, Octave or I whatever you like):
scala> def f(n: Int): Int = { if (n == 0) 3 else if (n == 1) 12 else (6 * f(n-1) - 9 * f(n-2)) }
f: (n: Int)Int
scala> for (i <- 0 until 20) println(f(i))
3
12
45
162
567
1944
6561
21870
72171
236196
767637
2480058
7971615
25509168
81310473
258280326
817887699
^
scala> def explicit(n: Int): Int = (Math.pow(3, n -1) * (3 * n + 9)).toInt
explicit: (n: Int)Int
scala> for (i <- 0 until 20) println(explicit(i))
3
12
45
162
567
1944
6561
21870
72171
236196
767637
2480058
7971615
25509168
81310473
258280326
817887699

Runtime of while loop pseudocode

I have a pseudocode which I'm trying to make a detailed analysis, analyze runtime, and asymptotic analysis:
sum = 0
i = 1
while (i ≤ n){
sum = sum + i
i = 2i
}
return sum
My assignment requires that I write the cost/runtime for every line, add these together, and find a Big-Oh notation for the runtime. My analysis looks like this for the moment:
sum = 0 1
long i = 1 1
while (i ≤ n){ log n + 1
sum = sum + i n log n
i = 2i n log n
}
return sum 1
=> 2 n log n + log n + 4 O(n log n)
is this correct ? Also: should I use n^2 on the while loop instead ?
Because of integer arithmetic, the runtime is
O(floor(ln(n))+1) = O(ln(n)).
Let's step through your pseudocode. Consider the case that n = 5.
iteration# i ln(i) n
-------------------------
1 1 0 5
2 2 1 5
3 4 2 5
By inspection we see that
iteration# = ln(i)+1
So in summary:
sum = 0 // O(1)
i = 1 // O(1)
while (i ≤ n) { // O(floor(ln(n))+1)
sum = sum + i // 1 flop + 1 mem op = O(1)
i = 2i // 1 flop + 1 mem op = O(1)
}
return sum // 1 mem op = O(1)

confused about a pair of recursion relations

thanks in advance for your help in figuring this out. I'm taking an algorithms class and I'm stuck on something. According to the professor, the following holds true where C(1)=1 and n is a power of 2:
C(n) = 2 * C(n/2) + n resolves to C(n) = n * lg(n) + n
C(n) = 2 * C(n/2) + lg(n) resolves to C(n) = 3 * n - lg(n) - 2
The first one I completely grok. As I understand the form, what's stated is that C(n) resolves to two sub-problems, each of which requires n/2 work to solve, and an additional n amount of work to split and merge everything. As such, for every division of the problem, the constant 2 is increased by a factor of ^k (where k is the number of splits), the 2 in n/2 is also increased by a factor of ^k for much the same reason, and the last n is multiplied by a factor of k because each split creates a multiple of k extra work.
My confusion stems from the second relation. Given that the first and second relations are almost identical, why isn't the result of the second something like nlgn+(lgn^2)?
The general result is the Master Theorem
But in this specific case, you can work out the math for a power of 2:
C(2^k)
= 2 * C(2^(k-1)) + lg(2^k)
= 4 * C(2^(k-2)) + lg(2^k) + 2 * lg(2^(k-1))
= ... repeat ...
= 2^k * C(1) + sum (from i=1 to k) 2^(k-i) * lg 2^i
= 2^k + lg(2) * sum (from i=1 to k) 2^(i) * i
= 2^k - 2 + 2^k+1 - k
= 3 * 2^k - k - 2
= 3 * n - lg(n) - 2

Resources